2020
DOI: 10.1186/s12885-020-07160-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of robotic- versus laparoscopic-assisted Total Gastrectomy for advanced gastric Cancer: a propensity score matching study

Abstract: Background: Few studies have been designed to evaluate the short-term outcomes between robotic-assisted total gastrectomy (RATG) and laparoscopy-assisted total gastrectomy (LATG) for advanced gastric cancer (AGC). The purpose of this study was to assess the short-term outcomes of RATG compared with LATG for AGC. Methods: We retrospectively evaluated 126 and 257 patients who underwent RATG or LATG, respectively. In addition, we performed propensity score matching (PSM) analysis between RATG and LATG for clinico… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
0
19
1
Order By: Relevance
“…For patients with advanced gastric cancer, Yang et al . also found that the blood loss of the RTG group was significantly lower than that of the LTG group (154.37 ± 89.68 vs 183.77 ± 95.39 mL, P = 0.004) [ 32 ]. The estimated blood loss in our case was 225 mL, which is more than that of RTG reported previously but to an acceptable extent.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with advanced gastric cancer, Yang et al . also found that the blood loss of the RTG group was significantly lower than that of the LTG group (154.37 ± 89.68 vs 183.77 ± 95.39 mL, P = 0.004) [ 32 ]. The estimated blood loss in our case was 225 mL, which is more than that of RTG reported previously but to an acceptable extent.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be attributed to the advanced robotic surgery systems, including an internal EndoWrist with seven degrees of freedom, three-dimensional vision, tremor filter, and short learning curve, which prevented injuries from the blood vessels and allowed precise dissection and high flexibility for surgeons [ 32 ]. Previous studies proved that one critical barrier to the wide RG application in clinical practice was high costs [ 12 , 13 , 16 , 17 , 33 , 34 ]. Our study also found that RADG group had higher medical cost than the LADG group.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported the postoperative complications, the results are still elusive [ 16 , 38 40 ]. A previous study demonstrated that RG showed similar postoperative morbidity to that of LG [ 16 ]. A recent meta-analysis also revealed no significant differences in the overall or severe complication rates between robotic and laparoscopic groups [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oncological short-term safety of robotic gastrectomy is reported comparable to open and probably laparoscopic resection [ 4 – 6 , 16 ]. A recent randomized controlled trial of robotic versus laparoscopic gastrectomy showed improved lymphadenectomy by the robotic approach for extraperigastric lymph nodes including station 12a.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a wide range of series, most Asian, indicates that minimally invasive robotic gastrectomy may also be performed with short-term oncologic outcome comparable to that of open surgery [ 2 , 3 ]. Available reports include series of robotic assisted and total robotic surgery for distal and total gastrectomy [ 4 – 6 ]. A recent randomized controlled trial reported benefits of robotic compared to laparoscopic distal gastrectomy in regard to morbidity, recovery, and lymphadenectomy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%